An ultra‐wideband monopole antenna with a gain enhanced performance using a novel split‐ring meta‐surface reflector. Issue 6 (30th March 2017) - Sen, Gobinda; Banerjee, Amartya; Kumar, Mukesh; Das, Santanu
ABSTRACT: This article presents the design of an ultra‐wideband monopole antenna with a gain enhanced performance using a novel double split ring metasurface reflector. A circular patch configuration is used here as the radiating element for the simplicity and reliability of such structures. The antenna radiates well beyond the ulta wideband (UWB) frequencies but the performance enhancement using double split ring Metasurface reflector is within UWB frequency. The periodic array of dual split ring patches with varying split angles placed in a columnar arrangement is responsible for the metasurface structure to reflect effectively in phase‐agreement over a broadband without affecting the impedance bandwidth of the principal radiator. With such a low profile setup (gap between antenna and reflector is in the order of at the lowest operating frequency of the antenna) the wideband gain‐enhanced characteristic makes the design versatile enough for numerous practical applications. A high increment in the antenna gain performance (nearly 5.5 dB) is recorded over the UWB frequency range. Experimental results are found to be in good agreement with the simulations. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1296–1300, 2017